Mengukur Respons Pengguna Bus Trans Metro Pasundan terhadap Program 'Buy the Service' menggunakan Rasch Model: Sebuah Studi Analitis - Maman Fathurohman, Cecep; Alia Randhiny, Zahra; Miftahuddin, Asep; Dijah Retno Pratiwi, Arundina; Rahmawati, Ati; Nurliawati, Nita (Pusat Pengembangan Sumber Daya Manusia Aparatur, 2023)
ABSTRACT This study aims to analyze the perspectives of users of Bus Trans Metro Pasundan regarding the government program